Patients as Rights Holders - Brännmark, Johan (The Hastings Center report, 2017)
Autonomy and consent have been central values in Western moral and political thought for centuries. One way of understanding the bioethical models that started to develop, especially in the 1970s, is that they were about the fusion of a long-standing professional ethics with the core values underpinning modern political institutions. That there was a need for this kind of fusion is difficult to dispute, especially since the provision of health care has in most developed countries become an ever more important concern of our political institutions, with governments playing a significant role in regulating and facilitating the provision of health care and in many countries even largely organizing it. There is, nevertheless, still room for dispute about how best to achieve this fusion and how to best think about autonomy and consent in a biomedical context. The simplest model we can have is probably about how being a person is largely about having the capacity of autonomous choice and that the main mode through which we exercise autonomy is by providing informed consent. Yet, liberal democracy's core idea that human beings have a high and equal value is also found in other accounts of the person. The human-rights framework provides an alternative model for thinking about personhood and about patient care. The human-rights approach is grounded, not in an account of autonomy (although it has something to say about autonomy), but in an account of the moral and political personhood that people possess merely by being human beings. In this approach, values like dignity and integrity, both highly relevant in a bioethical context, are identified as distinct values rather than being derived from and therefore reduced to respect for autonomous choice. The human-rights approach can supplement the problematic notion of autonomy that has been central to bioethics by placing this notion in a broader, strongly pluralistic framework.